Stability Analysis of Evasion Tunnels Using the Rock Tunneling Quality Index (Q-System) Method On the Construction of the Bagong Dam Trenggalek, East Java - Wardhany, Revi Eka; Yuwanto, Sapto Heru (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
The Bagong Dam evasion tunnel is part of the dam construction which functions to drain the water flow so that the dam work can be done. In planning the construction of evasive tunnels, it is necessary to study the geological, geotechnical and structural conditions of the tunnel. This study is intended to provide an overview of the subsurface and engineering geological conditions of the research area, so as to determine the stability of the evasion tunnel and then provide recommendations for the support to be used. The method used is the Rock Tunneling Quality Index (Q-System) method to determine the buffer to be used in the construction process. Based on the analysis of the subsurface geological conditions of the study area, there are three rock layers, namely: sandstone, breccia and limestone. In the Q-System analysis, the rock mass class value ranges from 0.451 to 0.651 with Very Poor quality and the rock mass class value is 1.162 with Poor quality. At the four drill points BH-09, BH-03, BH-10 and BH-11, the recommendation for support is obtained with the type of support (B+5) and SRF+B